Estudo de caso: análise da produtividade da mão de obra própria no serviço de revestimento cerâmico interno de um empreendimento real - Zuiani, Diogo dos Santos Tavares (2021)
In civil construction, labor represents approximately half of budget. In contrast, 47.3% of employees only have a high school diploma, directly reflecting on their remuneration and consequently, directly impacting on their productivity. However, the increase of productivity is related search for high profitability of construction companies. The productivity parameter, in turn, is measurable based on the collection of production data, contemplating information about the services and the teams responsible for the execution. Furthermore, the organization and analysis of these data benefits future planning of the company, where the actual indexes of its collaborators are applied. However, this analysis and effective application of data is often not performed. For this reason, in this work an analysis of the productivity of the own workforce is done, to verify whether the teams employed in the internal ceramic tile job had good productivity rates or not, in a project in the city of Apucarana-PR. In case of verified low productivity, proposals for improvements will be presented to the situations that influenced the service. To apply the methodology, the schedule of the project, the daily production control spreadsheet and the daily work reports are collected, for further organization of data and calculations of Unitary Production Ratio (UPR), in order to compare with the indexes presented by TCPO and SINAPI. As a result, only one team proved to be very productive, representing only 12.50% of the workforce employed in the service. Also, when compared to literature, this team only presented a better productivity index than SINAPI in the tile laying service, making the result even more restricted. Finally, it is noted that the idleness of labor at a construction site and the lack of production control are the main reasons why employees presented low productivity.